Evaluation of Postprocedural Pain and Quality-of-Life Improvement in Rural Patients with Chronic Venous Insufficiency Undergoing Endovenous Laser Ablation - Deshmukh, Sushmita Shailendra; Banode, Pankaj; Mohan, Abhinav (Journal of Clinical Interventional Radiology ISVIR, 2019)
Background Chronic venous insufficiency (CVI) manifests as unilateral or bilateral lower-limb venous hypertension causing pain, swelling, edema, and skin changes, among other symptoms. CVI affects patients’ socioeconomic status, is particularly seen in the young, and, in its severe manifestation, may have a debilitating effect on patients’ quality of life (QoL). The authors wanted to evaluate change in pain and QoL among rural patients after endovenous laser ablation (EVLA) treatment in a pilot study.Methods Twenty patients having CVI who opted for 1,470-nm EVLA treatment were enrolled at the Interventional Radiology department between July 2018 and September 2018. The authors evaluated pain using the visual analog scale (VAS) before and after EVLA procedure (standard protocol) of the affected vein. They also assessed QoL using the Aberdeen Varicose Vein Questionnaire before and 6 weeks after EVLA.Results The authors observed significant reduction in pain postprocedure versus preprocedure. Majority of the patients had improvement in itching and stasis dermatitis after the procedure. Rash and skin ulcers remained uncommon before and after EVLA. Also, after EVLA, fewer patients than before reported that the appearance of their diseased veins caused them concern (35 vs. 65% before EVLA), influenced their choice of clothing (45 vs. 80%), interfered with their work (40 vs. 90%), and interfered with their leisure activities (30 vs. 80%).Conclusion EVLA 1470nm procedure may help patients with CVI attain improved QoL and significant pain reduction.
Keywords: chronic venous insufficiency; endovenous laser ablation; varicose